A heavy oil hydroprocessing catalyst and preparation method thereof
By combining alumina support with different grain sizes in the catalyst, the channel diameter is controlled in a directional manner, so that it gradually increases along the radial direction of the sphere, forming a "horn-type" channel structure, the problem of insufficient diffusion performance of existing catalysts in heavy oil hydrotreatment is solved, efficient demetalization and desulfurization activities are achieved, and the activity stability is improved.
Patent Information
- Application Number
- CN202310002565.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-01-03
AI Technical Summary
During the hydrotreatment of heavy oil, existing catalysts are difficult to effectively remove impurities such as metals, sulfur and nitrogen, and their diffusion performance is insufficient, affecting the performance of deasphaltene and desulfurization.
The spherical alumina support is used as a catalyst. By combining support raw materials with different grain sizes, the accumulation state of particles is adjusted, and the diameter of the channels inside and on the surface of the catalyst sphere is controlled in a directionally, so that it gradually increases from the center of the sphere to the outer surface along the radial direction of the sphere, forming an open "horn-shaped" channel structure.
It improves the diffusion performance of the catalyst, enhances the hydrodemetalization and desulfurization activities, and has high activity stability, and is suitable for the hydrotreatment process of upstream heavy oil.
Smart Images

Figure DEST_PATH_IMAGE002 
Figure DEST_PATH_IMAGE008
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a heavy oil hydroprocessing catalyst and a preparation method thereof. Background Art
[0002] In recent years, with the heavier quality of crude oil resources, the growing demand for fuel oil and chemical products and increasingly stringent environmental regulations, the use of hydrogenation technology to convert heavy oil, including residual oil, into high-quality fuel oil and chemical products will help improve crude oil utilization, reduce environmental pollution, increase light oil yields and improve product quality.
[0003] The hydroprocessing process of heavy oil such as residue oil generally includes fixed bed, fluidized bed and slurry bed hydrogenation processes. Compared with other heavy oil hydrogenation technologies, fixed bed hydrogenation has become the preferred technology for residue oil hydrogenation due to its mature technology, low investment and operating costs, safe and simple operation, etc. In the fixed bed heavy oil hydroprocessing technology, in order to extend the operation cycle of the device, an upflow reactor (UFR) can be set at the front. In the upflow reactor, the raw oil and gas mixture flows upward from the bottom of the reactor through the catalyst bed, so that the entire catalyst bed is slightly expanded, the pressure drop is small, and at the same time, it can effectively reduce the metal content of the feed entering the subsequent reactor, protect the downstream fixed bed reactor, and better play the performance of the overall catalyst.
[0004] Inferior heavy oils such as residual oil contain a large amount of impurities such as metals (Fe, Ni and V, etc.), sulfur, nitrogen, and high residual carbon content. These impurities are mainly present in macromolecular compounds such as colloids and asphaltene. These substances have complex structures, large molecular sizes, and are difficult to diffuse. Moreover, after the metal is removed, it will be deposited on the catalyst surface and in the pores. Therefore, in order to maximize the performance of hydrogenation deasphalting, demetallization and desulfurization, the catalyst is required to have not only good reaction activity, but also excellent diffusion performance, so that macromolecules such as asphaltene can easily approach the inner surface of the catalyst.
[0005] Chinese patent CN 1665907A discloses an upflow hydrogenation catalyst, the carrier of which is composed of alumina, with a pore volume of 0.6-1.1 mL / g and a specific surface area of 110-190 m 2 / g, less than 35% of pores with diameters greater than 1000 angstroms, and a nitrogen desorption peak pore size of 80 to 140 angstroms, the catalyst is spherical or elliptical in shape, and the particle size is about 0.1 inches. The average pore size of the catalyst is relatively small, and compared with the catalyst prepared by the method of US 5472928, it has a higher hydrodesulfurization activity and a lower hydrodemetallization activity. In the heavy oil hydrogenation process, the heavy feedstock is first contacted with the catalyst prepared according to the method of US 5472928 under hydrodemetallization conditions, and then the product is contacted with the catalyst for hydrodesulfurization. The catalyst is suitable as a hydrodesulfurization catalyst, but requires a previously graded hydrodemetallization catalyst to extend the service life of the catalyst, and therefore, is not suitable for use alone in an upflow reactor.
[0006] U.S. Patent No. 4448896 adopts the method of adding a pore-enlarging agent to increase the pore volume of an alumina carrier and obtain smooth pores. The patent uses a pseudo-boehmite as a raw material, adds carbon black powder as a pore-enlarging agent, and obtains an alumina carrier through kneading, extrusion, drying and calcination. However, adding a small amount of carbon black powder easily forms "ink bottle"-shaped pores, and it is difficult to form effective through holes. Summary of the invention
[0007] The object of the present invention is to provide a spherical heavy oil hydroprocessing catalyst and a preparation method thereof, wherein the average pore diameter of the spherical catalyst gradually increases from the center of the sphere to the outer surface along the radial direction of the sphere, and the spherical catalyst is particularly suitable for an upflow heavy oil hydroprocessing process, and has the characteristics of good hydrodemetallization and desulfurization activity, high stability, etc.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] A heavy oil hydroprocessing catalyst, which is composed of a spherical alumina carrier and an active metal component loaded on the carrier, and the average pore diameter of the catalyst gradually increases from the center of the sphere to the outer surface along the radial direction of the sphere; according to the mercury intrusion method, the pore volume of the catalyst is 0.5-0.9 mL / g, the average pore diameter is 15-30 nm, and the specific surface area is 80-160 m 2 / g, the average pore diameter at the center of the sphere is 10~20nm, and the average pore diameter from 90% of the sphere diameter to the outer surface of the sphere is 25~40nm.
[0010] Furthermore, the active metal component is composed of at least one Group VI B metal and at least one Group VIII B metal component; in the form of metal oxides, the content of Group VI B metal in the catalyst is 1-10wt%, and the content of Group VIII B metal is 0.1-2wt%.
[0011] The preparation method of the heavy oil hydroprocessing catalyst comprises the following steps:
[0012] (1) Pseudo-boehmite PB-1, pseudo-boehmite PB-2 and carrier auxiliary materials are added to a mixer at different feeding rates, mixed, and a certain amount of peptizing agent is sprayed into the mixer to roll into balls, which are then dried and calcined to obtain a spherical alumina carrier;
[0013] (2) The spherical alumina carrier obtained in step (1) is impregnated with an aqueous solution of a metal salt containing a Group VI B metal and a Group VIII B metal, and the catalyst is obtained after drying and calcining.
[0014] Furthermore, the pseudo-boehmite PB-1 and PB-2 used in step (1) can be prepared by any method, such as precipitation method, alcohol aluminum hydrolysis method, hydrothermal method, etc., and the weight percentage of the two is 20~80:80~20.
[0015] Furthermore, the pseudo-boehmite PB-1 has a pore volume of 0.7-1.1 mL / g and a specific surface area of 150-250 m 2 / g, the crystal size d(120) is 5~15nm; the pore volume of the pseudo-boehmite PB-2 is 0.6~1.0mL / g, and the specific surface area is 60~150m 2 / g, and the crystal size d(120) is 30~50nm.
[0016] Furthermore, the carrier auxiliary material in step (1) is one or more of sesbania powder, methyl cellulose, hydroxymethyl cellulose, polyvinyl alcohol, and polyacrylamide, and the added amount thereof accounts for 0.5-5.0% of the weight of the obtained alumina carrier.
[0017] Furthermore, during the mixing in step (1), the pseudo-boehmite PB-1 is added to the mixer at an initial rate of 20-40% of the total amount per hour, and the total amount is reduced by 2-8% per hour. At the same time, the pseudo-boehmite PB-2 is added to the mixer at an initial rate of 0.1-10% of the total amount per hour, and the total amount is increased by 2-8% per hour. The carrier auxiliary material is added at a constant rate of 10-20% of the total amount per hour.
[0018] Furthermore, the peptizing agent in step (1) is an aqueous solution of any one or more of an inorganic acid and / or an organic acid, with a mass concentration of 1-10%, and an amount thereof added accounting for 2-8% of the weight of the obtained alumina carrier.
[0019] Furthermore, in step (1), the drying temperature is 20-120° C. and the time is 1-24 hours; and the calcination temperature is 500-900° C. and the time is 1-6 hours.
[0020] Furthermore, in step (2), the impregnation time is 0.1 to 24 hours; the drying temperature is 60 to 200° C., and the time is 1 to 24 hours; and the calcination temperature is 400 to 600° C., and the time is 1 to 6 hours.
[0021] The present invention combines carrier raw materials with different grain sizes and adjusts the stacking state of the particles to directionally control the pore diameter inside and on the surface of the alumina carrier sphere, ultimately causing the pore diameter of the spherical carrier to continuously increase from the center of the sphere to the outer surface, forming an open "trumpet-shaped" pore structure, thereby improving the diffusion performance.
[0022] Compared with the existing catalyst preparation methods, the advantage of the method of the present invention is that the diameter of the catalyst pores increases continuously from the center of the sphere to the outer surface, presenting an open "trumpet-shaped" pore structure with a large surface pore opening and unobstructed pores, so that the catalyst has high demetallization activity, desulfurization activity and activity stability. DETAILED DESCRIPTION
[0023] A heavy oil hydroprocessing catalyst, which is composed of a spherical alumina carrier and an active metal component loaded on the carrier, and the average pore diameter of the sphere increases gradually from the center to the outer surface along the radial direction of the sphere; measured by mercury intrusion method, the pore volume of the catalyst is 0.5-0.9 mL / g, the average pore diameter is 15-30 nm, and the specific surface area is 80-160 m 2 / g, the average pore diameter at the center of the sphere is 10~20nm, and the average pore diameter from 90% of the sphere diameter to the outer surface of the sphere is 25~40nm.
[0024] The active metal component is composed of at least one Group VI B metal and at least one Group VIII B metal component; in terms of metal oxide, the content of Group VI B metal in the catalyst is 1-10wt%, and the content of Group VIII B metal is 0.1-2wt%.
[0025] The preparation method of the heavy oil hydroprocessing catalyst comprises the following steps:
[0026] (1) Pseudo-boehmite PB-1 is added to the mixer at an initial rate of 20-40% of the total amount per hour, and the total amount is reduced by 2-8% per hour. At the same time, pseudo-boehmite PB-2 is added to the mixer at an initial rate of 0.1-10% of the total amount per hour, and the total amount is increased by 2-8% per hour. The carrier auxiliary material is added at a constant rate of 10-20% of the total amount per hour. The resulting mixture is then added to a sugar coating machine, and a certain amount of peptizing agent is continuously sprayed into the pot using a high-efficiency sprayer while the mixture is rolled to make the material roll into balls and grow, and then dried at 20-120°C for 1-24 hours, and calcined at 500-900°C for 1-6 hours to obtain a spherical alumina carrier;
[0027] (2) The spherical alumina carrier obtained in step (1) is impregnated with a metal salt aqueous solution containing a VI B metal and a VIII B metal for 0.1 to 24 hours, dried at 60 to 200° C. for 1 to 24 hours, and calcined at 400 to 600° C. for 1 to 6 hours to obtain the catalyst.
[0028] The weight percentage of the pseudo-boehmite PB1 and PB2 used is 20-80:80-20. The pore volume of the pseudo-boehmite PB-1 is 0.7-1.1 mL / g, and the specific surface area is 150-250 m 2 / g, the crystal size d(120) is 5~15nm; the pore volume of the pseudo-boehmite PB-2 is 0.6~1.0mL / g, and the specific surface area is 60~150m 2 / g, and the crystal size d(120) is 30~50nm.
[0029] The carrier auxiliary material is one or more of sesbania powder, methyl cellulose, hydroxymethyl cellulose, polyvinyl alcohol, and polyacrylamide, and the added amount thereof accounts for 0.5-5.0% of the weight of the obtained alumina carrier.
[0030] The peptizing agent is an aqueous solution of any one or more of inorganic acid and / or organic acid, with a mass concentration of 1-10%. The amount added is calculated based on the inorganic acid and / or organic acid accounting for 2-8% of the weight of the obtained alumina carrier.
[0031] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0032] Examples 1-4 illustrate the heavy oil hydroprocessing catalyst and its preparation method provided by the present invention.
[0033] Example 1
[0034] 1) Add 50 g of citric acid and 50 g of nitric acid (mass fraction 68%) into 1950 g of water, and stir to mix well to obtain a dilute acid solution A1;
[0035] 2) Weigh 23.4 g of basic nickel carbonate, 54.0 g of molybdenum trioxide, and 17.5 g of phosphoric acid, add 740 mL of deionized water, heat to 90 ° C, stir and dissolve, and prepare solution B1;
[0036] 3) Weigh 1200g of pseudo-boehmite PB-1 (pore volume 0.9mL / g, specific surface area 180m 2 / g, crystal size d(120) is 10nm), it is added to the mixer at an initial feeding rate of 380g / h, and is continuously added at a rate of 60g per hour. At the same time, 1200g of pseudo-boehmite PB-2 (pore volume is 0.8mL / g, specific surface area is 100m 2 / g, crystal size d(120) is 40 nm), which is added to the mixer at an initial feeding rate of 20 g / h, at a rate of 60 g per hour, and 60 g of sesbania powder is added to the mixer at a feeding rate of 10 g / h;
[0037] 4) The mixed material in the mixer is continuously conveyed to the sugar coating machine at a rate of 410 g / h while being mixed, and rolled into balls. During the balling process, the dilute acid solution A1 obtained in step 1) is continuously sprayed on the surface of the material with a high-efficiency sprayer while rolling, so that the balls are formed and grown. The balls are placed for curing for 24 hours, and then dried at 60°C for 12 hours, and then heated to 600°C at a rate of 2°C / min, and calcined at a constant temperature for 3 hours, and spherical alumina carrier SA-1 with a diameter of 3.0-3.5 mm is screened out;
[0038] 5) Take 1000 g of carrier SA-1, impregnate it with an equal volume of solution B1 obtained in step 2) for 2 h, cure it for 12 h, then dry it at 120°C for 12 h, and calcine it at 480°C for 2 h to obtain catalyst Cat-A.
[0039] Example 2
[0040] 1) Add 55 g of citric acid and 50 g of nitric acid (mass fraction 68%) to 2050 g of water, and stir to mix well to obtain a dilute acid solution A2;
[0041] 2) Weigh 23.4 g of basic nickel carbonate, 54.0 g of molybdenum trioxide, and 17.5 g of phosphoric acid, add 730 mL of deionized water, heat to 90 ° C, stir and dissolve, and prepare solution B2;
[0042] 3) Weigh 1220 g of pseudo-boehmite PB-1 (pore volume 0.9 mL / g, specific surface area 180 m 2 / g, crystal size d(120) is 10nm), it is added to the mixer at an initial feeding rate of 420g / h, and is continuously added at a rate of 72g per hour. At the same time, 1280g of pseudo-boehmite PB-2 (pore volume is 0.8mL / g, specific surface area is 100m 2 / g, crystal size d(120) is 40 nm), which is added to the mixer at an initial feeding rate of 20 g / h, at a rate of 72 g per hour, and 63 g of sesbania powder is added to the mixer at a feeding rate of 11 g / h;
[0043] 4) The mixed material in the mixer is continuously conveyed to the sugar coating machine at a rate of 451 g / h while being mixed, and rolled into balls. During the balling process, the dilute acid solution A2 obtained in step 1) is continuously sprayed on the surface of the material with a high-efficiency sprayer while rolling, so that the balls are formed and grown. The balls are placed for curing for 24 hours, and then dried at 60°C for 12 hours, and then heated to 600°C at a rate of 2°C / min, and calcined at a constant temperature for 3 hours, and spherical alumina carrier SA-2 with a diameter of 3.0-3.5 mm is screened out;
[0044] 5) Take 1000 g of carrier SA-2, impregnate it with an equal volume of solution B2 obtained in step 2) for 2 h, cure it for 12 h, then dry it at 120°C for 12 h, and calcine it at 480°C for 2 h to obtain catalyst Cat-B.
[0045] Example 3
[0046] 1) Add 55 g of citric acid and 55 g of nitric acid (mass fraction 68%) into 2200 g of water, and stir to mix well to obtain a dilute acid solution A3;
[0047] 2) Weigh 23.4 g of basic nickel carbonate, 54.0 g of molybdenum trioxide, and 17.5 g of phosphoric acid, add 750 mL of deionized water, heat to 90 ° C, stir and dissolve, and prepare solution B3;
[0048] 3) Weigh 1333 g of pseudo-boehmite PB-1 (pore volume 0.9 mL / g, specific surface area 180 m 2 / g, crystal size d(120) is 10nm), it is added to the mixer at an initial feeding rate of 400g / h, and then reduced by 60g per hour. At the same time, 1400g of pseudo-boehmite PB-2 (pore volume is 0.8mL / g, specific surface area is 100m 2 / g, crystal size d(120) is 40 nm), which is added to the mixer at an initial feeding rate of 10 g / h, at a rate of 60 g per hour, and 67 g of sesbania powder is added to the mixer at a feeding rate of 10 g / h;
[0049] 4) The mixed material in the mixer is continuously conveyed to the sugar coating machine at a rate of 420 g / h while being mixed, and rolled into balls. During the balling process, the dilute acid solution A3 obtained in step 1) is continuously sprayed on the surface of the material with a high-efficiency sprayer while rolling, so that the balls are formed and grown. The balls are placed for curing for 24 hours, and then dried at 60°C for 12 hours, and then heated to 600°C at a rate of 2°C / min, and calcined at a constant temperature for 3 hours, and spherical alumina carrier SA-3 with a diameter of 3.0-3.5 mm is screened out;
[0050] 5) Take 1000 g of carrier SA-3, impregnate it with an equal volume of solution B3 obtained in step 2) for 2 h, cure it for 12 h, then dry it at 120°C for 12 h, and calcine it at 480°C for 2 h to obtain catalyst Cat-C.
[0051] Example 4
[0052] 1) Add 55 g of citric acid and 50 g of nitric acid (mass fraction 68%) to 2050 g of water, and stir to mix well to obtain a dilute acid solution A4;
[0053] 2) Weigh 23.4 g of basic nickel carbonate, 54.0 g of molybdenum trioxide, and 17.5 g of phosphoric acid, add 750 mL of deionized water, heat to 90 ° C, stir and dissolve, and prepare solution B4;
[0054] 3) Weigh 1333 g of pseudo-boehmite PB-1 (pore volume 0.9 mL / g, specific surface area 180 m 2 / g, crystal size d(120) is 10nm), it is added to the mixer at an initial feeding rate of 360g / h, and then reduced by 48g per hour. At the same time, 1200g of pseudo-boehmite PB-2 (pore volume is 0.8mL / g, specific surface area is 100m 2 / g, crystal size d(120) is 40 nm), which is added to the mixer at an initial feeding rate of 20 g / h, at a rate of 48 g per hour, and 67 g of sesbania powder is added to the mixer at a feeding rate of 10 g / h;
[0055] 4) The mixed material in the mixer is continuously conveyed to the sugar coating machine at a rate of 390 g / h while being mixed, and rolled into balls. During the balling process, the dilute acid solution A4 obtained in step 1) is continuously sprayed on the surface of the material with a high-efficiency sprayer while rolling, so that the balls are formed and grown. The balls are placed for curing for 24 hours, and then dried at 60°C for 12 hours, and then heated to 600°C at a rate of 2°C / min, and calcined at a constant temperature for 3 hours, and spherical alumina carrier SA-4 with a diameter of 3.0-3.5 mm is screened out;
[0056] 5) Take 1000 g of carrier SA-4, impregnate it with an equal volume of solution B4 obtained in step 2) for 2 h, cure it for 12 h, then dry it at 120°C for 12 h, and calcine it at 480°C for 2 h to obtain catalyst Cat-D.
[0057] Comparative Example 1
[0058] 1) Add 50g of citric acid and 50g of nitric acid (mass fraction 68%) into 2000g of water, stir and mix well to obtain a dilute acid solution;
[0059] 2) Weigh 2400g of pseudo-boehmite PB-1 (pore volume 0.9mL / g, specific surface area 200m 2 / g, crystal size d(120) is 10nm), it is continuously conveyed to the sugar coating machine at a feeding rate of 400g / h for rolling into balls. During the ball forming process, the dilute acid solution obtained in step 1) is continuously sprayed on the surface of the material with a high-efficiency sprayer while rolling, so that the balls are formed and grown. The balls are placed for curing for 24h, then dried at 60℃ for 12h, and then heated to 600℃ at a heating rate of 2℃ / min, and calcined at a constant temperature for 3h, and spherical alumina carrier SC-1 with a diameter of 3.0~3.5mm is screened out;
[0060] 3) Weigh 23.4 g of basic nickel carbonate, 54.0 g of molybdenum trioxide, and 17.5 g of phosphoric acid, add 740 mL of deionized water, heat and stir to dissolve, and prepare solution B1;
[0061] 4) Take 1000 g of carrier SC-1, impregnate it with an equal volume of solution B1 obtained in step 3) for 2 h, cure it for 12 h, then dry it at 120°C for 12 h, and calcine it at 480°C for 2 h to obtain catalyst CC-1.
[0062] Comparative Example 2
[0063] 1) Add 50g of citric acid and 50g of nitric acid (mass fraction 68%) to 1950g of water, stir and mix to obtain a dilute acid solution;
[0064] 2) Weigh 1200g of pseudo-boehmite PB-1 (pore volume 0.9mL / g, specific surface area 180m 2 / g, crystal size d(120) is 10nm), it is added to the mixer at an initial feeding rate of 20g / h, and is continuously added at a rate of 60g per hour. At the same time, 1200g of pseudo-boehmite PB-2 (pore volume is 0.8mL / g, specific surface area is 100m 2 / g, crystal size d(120) is 40 nm), which is added to the mixer at an initial feeding rate of 380 g / h, and the rate of decreasing by 60 g per hour, and 60 g of sesbania powder is added to the mixer at a feeding rate of 10 g / h;
[0065] 3) The mixed material in the mixer is continuously conveyed to the sugar coating machine at a rate of 410 g / h while being mixed, and rolled into balls. During the balling process, the dilute acid solution obtained in step 1) is continuously sprayed on the surface of the material with a high-efficiency sprayer while rolling, so that the balls are formed and grown. The balls are placed for curing for 24 hours, and then dried at 60°C for 12 hours, and then heated to 600°C at a rate of 2°C / min, and calcined at a constant temperature for 3 hours, and spherical alumina carrier SC-2 with a diameter of 3.0-3.5 mm is screened out;
[0066] 4) Weigh 23.4 g of basic nickel carbonate, 54.0 g of molybdenum trioxide, and 17.5 g of phosphoric acid, add 740 mL of deionized water, heat to 90 ° C, stir and dissolve, and prepare solution B1;
[0067] 5) Take 1000 g of carrier SC-2, impregnate it with an equal volume of solution B1 obtained in step 4) for 2 h, cure it for 12 h, then dry it at 120°C for 12 h, and calcine it at 480°C for 2 h to obtain catalyst CC-2.
[0068] The physicochemical properties of the catalysts obtained in the examples and comparative examples are listed in Table 1.
[0069] The method for determining the average pore diameter of the catalyst from the center of the sphere to different parts of the outer surface is as follows: during the spherical formation process, when the spherical carrier grows to a certain particle size, the sample is taken out for drying and calcination, and the pore volume, specific surface area and average pore diameter of the sample are determined by mercury intrusion. The average pore diameter from the center of the sphere to different parts of the outer surface is calculated based on the relationship that the total pore volume and surface area of the sample are equal to the sum of each part (according to the Washburn equation, the contact angle of mercury is selected to be 130°, and the interfacial tension of mercury is selected to be 480 dyne / cm to calculate the pore diameter).
[0070] Table 1 Physicochemical properties of different catalysts
[0071]
[0072] From the results in Table 1, it can be seen that the diameter of the pores prepared in the example increases continuously from the center of the sphere to the outer surface, proving that the catalyst prepared therein has an open "trumpet-shaped" pore structure.
[0073] Application Examples
[0074] Density (20℃) is 1008kg / m 3The heavy oil hydrodemetallization and desulfurization performance of the catalysts obtained in the examples and comparative examples were evaluated using residual oil with a nickel content of 29 ppm, a vanadium content of 96 ppm, a sulfur content of 4.70wt%, and n-heptane insolubles of 5.3wt% as raw materials. The catalyst loading volume was 100 mL. The catalyst was sulfided by wet presulfurization before evaluation. The process conditions used to evaluate the catalysts in each example were the same (conditions: reaction temperature 380 ° C, hydrogen partial pressure 16 MPa, liquid hourly space velocity 1.0 h -1 , hydrogen to oil volume ratio is 300). The nickel and vanadium contents in the oil before and after hydrotreatment were determined by inductively coupled plasma emission spectrometry (ICP-AES) (for specific methods, see GB / T 37160). The sulfur content in the oil before and after hydrotreatment was determined by energy dispersive X-ray fluorescence spectrometry (for specific methods, see GB / T 17040). The metal removal rate and sulfur removal rate were calculated according to the following formula:
[0075] ;
[0076] .
[0077] The evaluation results are listed in Table 2.
[0078] Table 2 Evaluation results of demetallization and desulfurization activity of different catalysts
[0079]
[0080] The results in Table 2 show that the hydrodemetallization and desulfurization activities of the catalysts obtained in the examples are better than those of the catalysts obtained in the comparative examples.
[0081] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a heavy oil hydroprocessing catalyst, characterized in that: 1) Add 50 g of citric acid and 50 g of nitric acid into 1950 g of water, and stir to mix well to obtain a dilute acid solution A1; 2) Weigh 23.4 g of basic nickel carbonate, 54.0 g of molybdenum trioxide, and 17.5 g of phosphoric acid, add 740 mL of deionized water, heat to 90 ° C, stir and dissolve, and prepare solution B1; 3) Weigh 1200g of pseudo-boehmite PB-1, add it to the mixer at an initial feeding rate of 380g / h, and continue to add it at a rate of 60g per hour. At the same time, weigh 1200g of pseudo-boehmite PB-2, add it to the mixer at an initial feeding rate of 20g / h, and continue to add it at a rate of 60g per hour. And 60g of sesbania powder is continuously added to the mixer at a feeding rate of 10g / h. 4) The mixed material in the mixer is continuously conveyed to the sugar coating machine at a rate of 410 g / h while being mixed, and rolled into balls. During the balling process, the dilute acid solution A1 obtained in step 1) is continuously sprayed on the surface of the material with a high-efficiency sprayer while rolling, so that the balls are formed and grown. The balls are placed for curing for 24 hours, and then dried at 60°C for 12 hours, and then heated to 600°C at a rate of 2°C / min, and calcined at a constant temperature for 3 hours, and spherical alumina carrier SA-1 with a diameter of 3.0-3.5 mm is screened out; 5) 1000 g of carrier SA-1 was impregnated with an equal volume of solution B1 obtained in step 2) for 2 h, cured for 12 h, then dried at 120° C. for 12 h, and calcined at 480° C. for 2 h to obtain the catalyst; Wherein, the mass fraction of the nitric acid is 68%; The pore volume of the pseudo-boehmite PB-1 is 0.9 mL / g and the specific surface area is 180 m 2 / g, the crystal size d(120) is 10nm; The pore volume of the pseudo-boehmite PB-2 is 0.8 mL / g and the specific surface area is 100 m 2 / g, and the crystal size d(120) is 40nm.
Citation Information
Patent Citations
Catalyst for conversion processes
CN1665907A
Hydrogenation catalyst for desulfurization and removal of heavy metals
US4448896A
Catalyst, method and apparatus for an on-stream particle replacement system for countercurrent contact of a gas and liquid feed stream with a packed bed
US5472928A
Inferior heavy oil hydrodemetallization catalyst and preparation method thereof
CN104646005A
Residual oil hydrodemetallization and desulfurization catalyst and preparation method thereof
CN110201691A